Credit Lines in Lithuanian Banking - Bagdonas, Darius; Staškevičius, Juozapas Audvydas (Ekonomika, 1997)
The article deals with (he main methods of credit line utilization. Credit lines established by foreign banks and other financial institutions for Lithuanian commercial hanks mean that Lithuanian hanks arc trusted anti recognized by foreign financial institutions. They allow Lithuania to effectively perform various foreign exchange anti money market tasks and trade the financial resources of foreign financial institutions, financing international trade as well as disclosing new possibilities for Lithuanian enterprises to get cheap financial resources for the realization of strategic and long-term projects.